Factor Related to Occupational Accidents Of Woodworkers At Furniture Manufacturers in Larantuka Sub-Distric Of East Flores Regency - Kedang, Vinsensia Barek; Adu, Apris A.; Sahdan, Mustakim (Timorese Journal of Public Health, 2020)
A workplace accident is an unexpected accident in a work place, which is a direct result of performing a job or the work environment or an accident that occurs while the job is being carried out. Workplace accidents are caused by various factors, such as age, gender, educational level, working period and knowledge of the workers. The work factors includes working hours, work units, workload, fatigue and wearing PPE. The working environment includes room temperature, lighting and noise. The purpose of this study is to analyze the relationship between age, working period, working hours, workload, fatigue, wearing PPE and noise to the incidence of workplace accidents for furniture workers in Larantuka Sub-district, East Flores Regency. This was an analytical survey using a cross sectional study design. The population in this study was all 40 furniture workers in Larantuka Sub-district, East Flores Regency. The sample of this study was selected using total sampling technique, in which the number of samples was the same as the population (40 people). The findings indicated a significant relationship among working period, workload, fatigue, wearing PPE and noise with workplace accidents for furniture workers where the p.value was < alpha (0.05). There was no significant relationship between age and working hours with the incidence of workplace accidents for furniture workers where p.value was > alpha (0.05). It is expected that the furniture companies have to monitor and control risk factor in workplaces, so that the furniture workers are avoided from the workplace accidents.